Patterns of Blunt and Cigar Use in the United States, 2015-2019 - Jensen, Jessica K; Ganz, Ollie; Tomaino, Marisa; Glasser, Allison M; Sterling, Kymberle; Delnevo, Cristine D; Bover Manderski, Michelle T (Nicotine & tobacco research, 2025)
The use of cigars for blunts (ie, cannabis rolled in cigar paper) is well documented; the prevalence of cigar and blunt use and associated characteristics are less studied. Pooled data from the 2015-2019 National Survey on Drug Use and Health were analyzed in 2023. Respondents aged 12+ who reported past 30-day cigar use were categorized into three mutually exclusive use categories: (1) exclusively cigars, (2) exclusively blunts, and (3) both cigars and blunts. We examined associations between cigar-blunt use categories and sociodemographic characteristics. Among respondents aged 12+ who reported past 30-day cigar use, 48.6% (95% confidence interval [CI] = 47.6 to 49.6) reported exclusive cigar use; 44.3% (95% CI = 43.3 to 45.3) reported exclusive blunt use; and 7.2% (95% CI = 6.8 to 7.6) reported use of cigars and blunts. The prevalence differed by age, with exclusive blunt use most prevalent among youth (72.5% [95% CI = 70.7 to 74.3]) and young adults (62.4% [95% CI = 61.4 to 63.5]), and exclusive cigar use most prevalent among adults 26+ (61.2% [95% CI = 59.8 to 62.5]). Exclusive blunt users smoked more days in the past month (17.5; 95% CI = 16.8 to 18.2), compared to 13.8 days (95% CI = 13.2 to 14.4) for cigar and blunt users, and 7.7 days (95% CI = 7.5 to 8.0) for exclusive cigar users. There were significant differences in sociodemographic characteristics, with female (41.6%; 95% CI = 40.3 to 42.9) and Hispanic (18.2%; 95% CI = 17.3 to 19.2) participants more likely to report exclusive blunt use. Exclusive blunt use was the most prevalent pattern of past 30-day cigar use among youth and young adults. Those who use cigars as blunts smoked more cigars per month, suggesting this may be an important group for education and policy efforts. Studies that aggregate cigars and blunts into one group may limit potentially meaningful subgroup risk profiles. Additionally, when assessing cigar use, particularly among youth and young adults, it is important to consider blunt use to avoid missing youth who exclusively use cigars for blunts and may not consider blunts as cigar products. Accurate measurement may better inform tobacco and cannabis regulatory actions. Finally, given the high prevalence of blunt use among youth and young adults identified in the present study, additional education efforts may be warranted for this population to reduce long-term risks.